Care professionals’ experiences within a multidisciplinary and cross-sectorial intervention for childbearing women and families in vulnerable positions: a focus group study - Lene Nygaard; Deborah Lee Davis; Inge Olga Ibsen; Maiken Pontoppidan; Ellen Aagaard Nøhr; Dorthe Susanne Nielsen (International Journal of Qualitative Studies on Health & Well-Being)
Inequality in health persists in childbearing families in socially or mentally vulnerable positions. The FACAM project was developed as an intervention aiming to enhance health outcomes for childbearing families. Purpose The aim of this study was to gain a deeper understanding of the experiences and perspectives of care professionals in multidisciplinary and cross-sectorial collaboration, and their experiences of interactions with childbearing families within the context of the FACAM project. Methods Eight focus groups were conducted with 32 multidisciplinary care professionals working with childbearing families in vulnerable positions. A thematic analysis was conducted, with positioning theory as the theoretical framework focusing on storylines, positioning and speech-acts. Results Two overall themes were constructed. Theme one: Cross-sectorial collaboration and the influence on the care provided. Theme two: Interaction with and assessment of women and families’ care needs and their influence on the care provided, with three subthemes; a) Establishment of a trustful relationship, b) Assessments of vulnerable positions in relation to function in everyday life, c) Interactions with the woman or family depending on their needs. Conclusion Care professionals found needs-adapted and tailored care meaningful. Well-functioning multidisciplinary and cross-sectorial collaboration was important to support the families.